Who engages in explicit knowledge creation after graduation? Evidence from the alumni impact survey of a large Canadian public university. Issue 1 (2nd January 2022) - Yang, Jinli; Roy, Stephannie; Goel, Vivek
ABSTRACT: While researchers and policymakers have sought to understand factors that affect research productivity of universities and entrepreneurship activities of graduates, we know little about the graduates in the workforce who engage in knowledge creation. This study employs data from an alumni impact survey ( N  = 12, 504) and alumni database of a large Canadian public university to determine the characteristics of alumni who have engaged in knowledge creation. The results suggest that although having a postgraduate degree is a significant predictor of engaging in knowledge creation, 36.7% of those without such a degree have also generated new knowledge. Other significant predictors include gender, age, extracurricular leadership experience, degree, discipline, being the first person of one's immediate family to attend a university, and a degree from abroad. The effects of the characteristics are different for alumni with and without a postgraduate degree. Implications for university-wide policies on research training and student experience are discussed.